Analysis of Cryptographic Libraries(SSL/TLS) - Prasad Kannojia, Suresh; Kurmi, Jitendra (International Journal of Computer Sciences and Engineering, 2021)
Secure communication in Computer Network is very important which can be achieved by Transport Layer Security (TLS) protocol. Various libraries have been created for the implementation of TLS functions by the researchers, of which each has wide support of the encryption algorithms, key exchange mechanism from which one can implement TLS for secure communications. In this paper, to find the best suitable SSL/TLS library, relative analysis of the six widely used libraries has been done based on various affecting parameter such Languages, Cryptographic Token Interface - PKCS#11, Thread Safety, and CPU Assisted Cryptography with AES-NI. Any organization can use an effective and efficient library that will provide the appropriate security and fulfill the expectation of the application.